2023
DOI: 10.3390/jcm12103477
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study Investigating the Safety and Efficacy of Nanoliposomal Irinotecan in Elderly Patients with Unresectable Pancreatic Cancer

Abstract: Although nanoliposomal irinotecan combined with 5-fluorouracil and leucovorin (nal-IRI+5-FU/LV) has been used to treat first-line resistant unresectable pancreatic cancer, the efficacy and safety data among the elderly remain limited. We retrospectively analyzed clinical outcomes among elderly patients. Patients treated with nal-IRI+5-FU/LV were assigned to the elderly (≥75 years) and non-elderly (<75 years) groups. Herein, 85 patients received nal-IRI+5-FU/LV, with 32 assigned to the elderly group. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…There are many reports on predictors of treatment-response by nal-IRI-based therapy. In particular, CAR, NLR, GPS, total bilirubin, carcinomatosis, and previous treatment with irinotecan have been significantly associated with overall survival (3)(4)(5)(6)(7)(8). However, no study has reported the risk factors for the adverse events during nal-IRI/FL treatment based on the analysis of factors other than the UGT1A1 polymorphism in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many reports on predictors of treatment-response by nal-IRI-based therapy. In particular, CAR, NLR, GPS, total bilirubin, carcinomatosis, and previous treatment with irinotecan have been significantly associated with overall survival (3)(4)(5)(6)(7)(8). However, no study has reported the risk factors for the adverse events during nal-IRI/FL treatment based on the analysis of factors other than the UGT1A1 polymorphism in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this trial result, the regulatory agency in Japan has approved the nal-IRI plus 5-FU and L-leucovorin (nal-IRI/FL) combination therapy. Particularly interesting studies focused on predictors of treatment-response by nal-IRI-based therapy in patients with pancreatic cancer have indicated that C-reactive protein/albumin ratio (CAR), neutrophil/lymphocyte ratio (NLR), Glasgow prognostic score (GPS), total bilirubin, carcinomatosis, and previous irinotecan treatment are significantly associated with overall survival (3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 99%